Jingle Bells - Hapka, Cathy (Horse diaries, 2014)
In 1915 Wisconsin, a farm horse named Jingle Bells worries that his family will replace him when the older son brings home a brand new Model-T Ford car. Includes facts about Clydesdale horses.